Engineering oncolytic vaccinia virus to redirect macrophages to tumor cells. Issue 2 (12th July 2020) - Cao, Felicia; Nguyen, Phuong; Hong, Bangxing; DeRenzo, Christopher; Rainusso, Nino C.; Rodriguez Cruz, Tania; Wu, Meng‐Fen; Liu, Hao; Song, Xiao‐Tong; Suzuki, Masataka; Wang, Lisa L.; Yustein, Jason T.; et al.
Abstract: Oncolytic virotherapy has been tested in numerous early phase clinical studies. However, the antitumor activity of oncolytic viruses thus far has been limited. Numerous strategies are being explored to enhance their antitumor activity by activating the adaptive arm of the immune system. We reasoned that it might also be possible to engineer oncolytic viruses to redirect tumor‐associated macrophages to tumor cells for therapeutic benefit. We engineered an oncolytic vaccinia virus (VV) to disrupt the CD47/SIRPα interaction by expressing a chimeric molecule that consists of the ectodomain of SIRPα and the Fc domain of IgG4 (SIRPα‐Fc‐VV). SIRPα‐Fc‐VV readily replicated in tumor cells and redirected M1 as well as M2 macrophages to tumor cells in vitro. In contrast, control VVs that either encoded YFP (YFP‐VV) or SIRPα (SIRPα‐VV) did not. In vivo, SIRPα‐Fc‐VV had greater antitumor activity than YFP‐VV and SIRPα‐VV in an immune competent osteosarcoma model resulting in a significant survival advantage. Pretreatment with cytoxan further augmented the antitumor activity of SIRPα‐Fc‐VV. Thus, arming oncolytic viruses with SIRPα‐Fc may present a promising strategy to enhance their antitumor activity for the virotherapy of solid tumors.